Macrostructure of the texts of court decisions on the example of Polish and French judgments - Nowak-Korcz, Paulina (Specialized Languages in Intercultural Communication, 2020)
This article concerns the comparative analysis of Polish and French Civil Court judicial decisions. Although the analyzed texts of judicial decisions are rooted in the culture of civil law and feature many similarities between the systems of Polish and French laws, both Polish and French judgments differ at the level of the global, graphic structure of texts. The article discusses the macrostructure of Polish and French judgments and their importance in the translation process. Next, selected problems emerging during their translation are presented in order to familiarize translators and interpreters with difficulties arising from the specific style and form of civil law judgments. The study is based on the analysis of comparable texts, as well as the model of pragmatic translation of legal terms proposed by Kierzkowska (2002). In addition, it is based on empirical observations of expressions and structures typical of Polish and French judgments. The author also emphasizes the special role of comparable texts in specialised translation and advocates the need to distinguish comparable and parallel texts.